Choosing Death So That Others May Live: The Permissibility of Living Vital Organ Donation - DIDDE BOISEN ANDERSEN; Andreas Albertsen (The Journal of Medicine and Philosophy: A Forum for Bioethics and Philosophy of Medicine, 2026)
Abstract The conventional admiration for supererogatory acts, where individuals sacrifice themselves to aid others, contrasts sharply with the hesitance observed when considering the living donation of vital organs. This article challenges this inconsistency, contending that no relevant moral difference exists between other celebrated supererogatory acts and the act of living vital organ donation. I go beyond the proposed concept of organ donation euthanasia, advocating for the moral permissibility of living vital organ donation, even though one is not facing imminent death from other causes.